From criticism to reform. Political and economic thought, and the view of the crown on complaints of corruption from the Indies - De Orellana Sánchez, Juan Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Based on the study of extra-judicial accusations made from Lima, Puebla, Loja and Potosí against the excesses of the viceroys, their servants, and other authorities; as well as of legal and political treaties, this article studies the concept of corruption in the kingdoms of the Indies, and contributes to the understanding of the significance and characteristics of corruption in the Hispanic world in the 17th century. As a result, it is revealed that the individuals and the institutions of the cities of the Indies were key to the expansion and refinement of the concept of corruption which, at the same time, led to a change in the political practice and culture, at the local-American level and that of the crown. This was reflected in the change in the legislation of the Indies to support local groups, sanction those who did not serve well, and regulate the power and performance of the main representatives of the crown. Likewise, the discourse of corruption generated in America included the reflection on how the kingdom of the indies was supposed to work in economic terms and to propose reforms in order to control it.